2008
DOI: 10.1007/s11695-007-9331-8
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Effectiveness of the Intragastric Balloon for Obesity. A Meta-Analysis

Abstract: The use of the BIB, within a multidisciplinary weight management program, is a short-term effective treatment to lose weight, but it is not yet possible to verify its capacity to maintain the weight lost over a long period of time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
256
5
18

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 374 publications
(297 citation statements)
references
References 29 publications
(36 reference statements)
18
256
5
18
Order By: Relevance
“…In one subject, a serious adverse event occurred (persistent vomiting, abdominal pain, and gastroesophageal reflux), leading to premature removal of the IGB. These findings are similar to previous studies, where gastrointestinal events were experienced post-insertion (32). Our proactive management of these events with pharmacotherapy, commenced at the time of IGB insertion (for 1-2 weeks prior in the case of PPIs), plus the implementation of a specific transitional diet focused on limiting foods which might irritate the stomach, are important in reducing the severity and/or duration of these events.…”
Section: Discussionsupporting
confidence: 87%
“…In one subject, a serious adverse event occurred (persistent vomiting, abdominal pain, and gastroesophageal reflux), leading to premature removal of the IGB. These findings are similar to previous studies, where gastrointestinal events were experienced post-insertion (32). Our proactive management of these events with pharmacotherapy, commenced at the time of IGB insertion (for 1-2 weeks prior in the case of PPIs), plus the implementation of a specific transitional diet focused on limiting foods which might irritate the stomach, are important in reducing the severity and/or duration of these events.…”
Section: Discussionsupporting
confidence: 87%
“…Previously published results revealed an average weight loss of 12-15 kg over 6 months with an excellent safety profile [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] . The Spatz Adjustable balloon was introduced in 2010 as the first IGB approved for 1 year implantation while featuring an adjustability function that afforded balloon volume changes as needed.…”
Section: Introductionmentioning
confidence: 99%
“…It was approved in May 2010 in all 27 countries of the European Union for patients with BMI > 27 that failed previous attempts at weight loss (certificate number 10 0384 QS/NB). The adjustability function was developed to address the issues related to other standard 6 months IGBs; 1) reduced efficacy after 2 to 3 months from implantation 3,16 , and 2) significant nausea, vomiting, and discomfort in the early implantation period, necessitating balloon extraction in 4-7% of patients 1,2 17,18 . In 2012, the Spatz3 adjustable balloon was approved for 1 year implantation with the same features as the original Spatz balloon, but with a softer and smaller profile catheter.…”
Section: Introductionmentioning
confidence: 99%
“…Intragastric balloons were first proposed as an aid for weight loss more than 20 years ago [22]. Since then, Bioenterics fluid-filled balloons (BIB) have been sited endoscopically into the stomach typically for six months, to induce satiety by reducing the stomach capacity, thereby reducing food intake and encouraging weight loss amongst obese populations [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review by Dumonceau (2008) of BIB treatments reported a mean weight loss of 17.8 kg, ranging from 4.9 kg -28.5 kg [21]. Imaz (2008) reported a weight loss of 14.7 kg at 6 months representing a 32.1% loss of excess weight and a BMI change of 5.7 [22]. Building on the learning from weight management literature, treatment with BIB should be proposed in the setting of a multidisciplinary framework [22] to help promote and sustain the lifestyle changes adopted [10].…”
Section: Introductionmentioning
confidence: 99%